Mechanical-property tests on assembled-type light steel modular house. (May 2020) - Zhang, Jun-Feng; Zhao, Jun-Jie; Yang, Da-Yong; Deng, En-Feng; Wang, Huan; Pang, Shi-Yun; Cai, Li-Ming; Gao, Shu-Cai
Abstract: The assembled-type light steel (ATLS) modular house—a modular building and an emerging type of eco-friendly architecture—consists of a bottom frame and a top frame that are connected with columns and high-strength bolts. It has the advantages of superior quality, a shorter construction time, and less resource wastage compared with traditional construction. In this study, two full-scale models were tested to obtain the vertical bearing capacity and the horizontal stiffness. A three-dimensional nonlinear finite-element (FE) model was established using the general-purpose FE software ABAQUS and validated against the test results. The load–displacement and load–stress curves were analysed and compared with the result of finite element analysis (FEA). The results indicated that the bottom frame beam of the ATLS modular house had a good deformation capacity and low rigidity. The horizontal stiffness of the ATLS modular unit was 1.21kN/mm and the results of FEA exhibited a minor difference about 1.65% comparing with the test result. The buckling mode and load–displacement curves in the FE analysis exhibited good agreement with the test results. Highlights: Two full-scale ATLS modules were tested under vertical load and horizontal load, respectively. The failure modes of ATLS modules under vertical load and horizontal load were obtained. The mechanical behaviors of ATLS modules were investigated and evaluated. Finite element model was established and verified against the test results.